The importance of economic freedom and political stability on the relationship between ESG and firm performance and value in emerging markets - Tubay, Jerwin B. (Animo Repository, 2022)
This study tests the moderating effect of country-level factors, economic freedom, and political stability, on the relationship between the company's sustainability activities as measured by its ESG score and its firm performance and value. As supported by the concept of Institutional Theory, the moderating effect was examined using a Multilevel Modelling approach. The samples gathered were from publicly listed companies in emerging countries across the Asia-Pacific Region. The results show that economic freedom does not significantly affect the relationship of ESG with the firm performance and value. At the same time, political stability was a significant moderator of the relationship between ESG and firm value. Hence, companies operating in emerging countries of the Asia-Pacific Region were recommended to invest heavily in sustainable activities and practices to boost the company valuation if they are working in a country with a high level of political stability. On the other hand, the investment managers are advised to consider the country's political stability before picking up investments in emerging countries included in the Asia-Pacific Region.